Synthesis and Absolute Configuration of Two Natural Phenolic Homobenzyl Esters. Issue 7 (2nd June 2015) - Xu, Murong; Zhu, Shijun; Xu, Zejun; Wu, Yikang; Gao, Po
Abstract Two recently identified natural phenolic homobenzyl esters, isolated from Phragmipedium calurum (an orchid) and Eupatorium fortunei TURCZ (a perennial herb in the Asteraceae family), respectively, were synthesized in enantiopure forms. By comparison of the optical rotations for the synthetic and the natural samples, the absolute configurations for the natural products were reliably assigned. The synthesis also enables establishment of the absolute configuration of a closely related natural homobenzyl alcohol and provided for the first time complete physical and spectroscopic data for two other natural homobenzyl esters.